Efektivitas Pengawasan dan Monitoring Keuangan Daerah Terhadap Peningkatan PAD Kota Bandung Tahun 2023 - Adji Firmansyah; Muhammad Alka Gustiyan Rojabi; Eva Hany Fanida; Revienda Anita Fitrie (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Local Own-Source Revenue (PAD) is a key indicator of local government fiscal autonomy and is significantly influenced by the effectiveness of financial oversight and monitoring. This study aims to analyse the effectiveness of local financial oversight and monitoring in driving an increase in Bandung City’s PAD in 2023. The study employs a qualitative approach using a documentary study method. Data was collected through a review of PAD realisation reports, the Regional Revenue and Expenditure Budget (APBD) documents, internal oversight reports, and regulations relating to local revenue management. The data was analysed descriptively and analytically by comparing PAD realisation achievements against the oversight mechanisms and monitoring systems implemented during 2023. The research findings indicate that strengthening internal oversight and implementing a digital monitoring system contribute positively to increasing PAD, particularly in the local tax sector. More systematic reporting and monitoring transparency encourages improved compliance and reduces the potential for revenue leakage. However, this study also identified constraints regarding limited human resources and data integration between agencies. Overall, effective financial oversight and monitoring play a crucial role in supporting accountable and sustainable increases in PAD.